Drug-Induced Rhabdomyolysis Atlas (DIRA) for idiosyncratic adverse drug reaction management. Issue 1 (January 2019) - Wen, Zhining; Liang, Yu; Hao, Yingyi; Delavan, Brian; Huang, Ruili; Mikailov, Mike; Tong, Weida; Li, Menglong; Liu, Zhichao
Highlights: A drug-induced rhabdomyolysis (DIR) classification scheme was developed based on drug labeling information. The first web-based application for DIR information was built. Key aspects of DIR management inducing precision dosing, concomitant use, and predictive modeling were emphasized and exemplified. Abstract : Drug-induced rhabdomyolysis (DIR) is an idiosyncratic and fatal adverse drug reaction (ADR) characterized in severe muscle injuries accompanied by multiple-organ failure. Limited knowledge regarding the pathophysiology of rhabdomyolysis is the main obstacle to developing early biomarkers and prevention strategies. Given the lack of a centralized data resource to curate, organize, and standardize widespread DIR information, here we present a Drug-Induced Rhabdomyolysis Atlas (DIRA) that provides DIR-related information, including: a classification scheme for DIR based on drug labeling information; postmarketing surveillance data of DIR; and DIR drug property information. To elucidate the utility of DIRA, we used precision dosing, concomitant use of DIR drugs, and predictive modeling development to exemplify strategies for idiosyncratic ADR (IADR) management.